Influenza Pandemic Periodicity, Virus Recycling, and the Art of Risk Assessment - Walter R. Dowdle (Emerging Infectious Diseases, 2006)
Influenza pandemic risk assessment is an uncertain art. The theory that influenza A virus pandemics occur every 10 to 11 years and seroarcheologic evidence of virus recycling set the stage in early 1976 for risk assessment and risk management of the Fort Dix, New Jersey, swine influenza outbreak. Additional data and passage of time proved the theory untenable. Much has been learned about influenza A virus and its natural history since 1976, but the exact conditions that lead to the emergence of a pandemic strain are still unknown. Current avian influenza events parallel those of swine influenza in 1976 but on a larger and more complex scale. Pre- and postpandemic risk assessment and risk management are continuous but separate public health functions.